2024
DOI: 10.1021/acsomega.3c07822
|View full text |Cite
|
Sign up to set email alerts
|

Nanocomposite Marvels: Unveiling Breakthroughs in Photocatalytic Water Splitting for Enhanced Hydrogen Evolution

Vikash Kumar,
Gajendra Prasad Singh,
Manish Kumar
et al.

Abstract: An overview of the significant innovations in photocatalysts for H 2 development, photocatalyst selection criteria, and photocatalytic modifications to improve the photocatalytic activity was examined in this Review, as well as mechanisms and thermodynamics. A variety of semiconductors have been examined in a structured fashion, such as TiO 2 -, g-C 3 N 4 -, graphene-, sulfide-, oxide-, nitride-, oxysulfide-, oxynitrides, and cocatalyst-based photocatalysts. The techniques for enhancing the compatibility of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 193 publications
(282 reference statements)
0
1
0
Order By: Relevance
“…Despite various efforts being made to synthesize semiconductor materials, their performance remains unsatisfactory. Numerous photocatalysts have been utilized for photocatalytic hydrogen generation, i.e., TiO 2 , g-C 3 N 4 , ZnO, WO 3 , SrTiO 3 , CuInS 2 , BaTaO 2 N, Bi 2 MoO 6 , Znln 2 S 4 , BiVO 4 , graphene oxide, MOF, and perovskite materials . It has been reported that the most dominant challenges confronted in photocatalytic water splitting are undesirable e – /h + recombination, narrow visible-light response range, and inefficient surface catalytic overpotential .…”
Section: Introductionmentioning
confidence: 99%
“…Despite various efforts being made to synthesize semiconductor materials, their performance remains unsatisfactory. Numerous photocatalysts have been utilized for photocatalytic hydrogen generation, i.e., TiO 2 , g-C 3 N 4 , ZnO, WO 3 , SrTiO 3 , CuInS 2 , BaTaO 2 N, Bi 2 MoO 6 , Znln 2 S 4 , BiVO 4 , graphene oxide, MOF, and perovskite materials . It has been reported that the most dominant challenges confronted in photocatalytic water splitting are undesirable e – /h + recombination, narrow visible-light response range, and inefficient surface catalytic overpotential .…”
Section: Introductionmentioning
confidence: 99%